Green Synthesis and Electrochemical Study of Undoped and Doped Al2O3 Nanoparticles Using Hibiscus rosa-sinensis Leaves Extract - Farzana Haider; Gul Asimullah Khan Nabi; Kiran Shah; Kafeel Ahmad Khan; Haseeba Khan (Indonesian Journal of Chemistry, 2023)
In the present work, nanoparticles of Al2O3, Cu-Al2O3, and Ni-Al2O3 were prepared using Hibiscus rosa-sinensis plant leaf extract through co-precipitation method. The prepared nanomaterials were characterized through TGA, EDX, SEM, UV-Vis, XRD, and FTIR instruments. The electrochemical behavior of Al2O3, Cu-Al2O3, and Ni-Al2O3 has been studied in DMF solution in the potential ranges from −1.5 to 1.5 V. The nanoparticles are thermally stable, according to the TGA, and the XRD patterns revealed that all the Al2O3, Cu-Al2O3, and Ni-Al2O3 particles were crystalline, with the mean sizes of 12.44, 34.61, and 31.63 nm, respectively. The cyclic voltammogram showed a cathodic peak (Epc) at 0.49 V with an anodic counterpart (Epa) at 0.49 V [E1/2 = 1.748 V]. The optical band gaps of Al2O3, Cu-Al2O3, and Ni-Al2O3 were 3.8, 3.2 and 3.65 eV, owed a cathode. It is observed that the electrochemical behavior of Ni-Al2O3 was identical to that of Al2O3 and Cu-Al2O3. The anodic and cathodic peak values rise with the scan rate. The one-electron oxidation and reduction processes are reversible, as seen by the shifting cathodic peak value toward higher negative values. All cycles exhibit absorption has a constant anodic current. This result indicated the diffusion-based redox process.